Level Of Physical Condition Of Futsal Athletes At Sma Negeri 1 Teluk Kuantan Kuantan Singingi - Mirza Piliyang Zador; Oki Candra; Toktong Parulian (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The aim of this research was to see the level of physical condition of futsal athletes at SMA Negeri 1 Taluk Kuantan. Based on the results of observations of futsal athletes at SMA Negeri 1 Taluk Kuantan, it was discovered that their physical condition had never been checked at all by the coach, it was only seen that the students' physical condition was not good. It was proven that when doing drills several times, some students felt tired quickly. Poor physical condition causes the school athletes' performance to fluctuate. Coaches also complained about the physical condition of futsal athletes which caused the athlete's performance when competing to be unstable. Students really need excellent physical condition when competing to carry out the coach's tactics and strategies. Poor physical condition can result in decreased ball control, disrupted strategy and can result in defeat. Apart from that, when chasing the ball the athlete looks slow, then his movements look less agile and his shooting kick has less power so that his kick seems weak. The tests used in this study used futsal physical condition tests including leg muscle strength tests (leg dynamometer), speed tests (30 meter sprint), flexibility tests (sitting and reaching), agility tests (shuttle run), leg muscle explosive power tests. (vertical jump) and endurance test ( balke test). The sample in this study was 20 futsal athletes from SMA Negeri 1 Taluk Kuantan. From the results of tests carried out in the field, results were obtained in the "Perfect" category, proven by an average score of 17.70 or in the interval 9.6 – 10.